FPGA Implementation of a SAR Two-dimensional Autofocus Approach - Guo Jiangzhe; Zhu Daiyin; Mao Xinhua (Leida xuebao, 2016)
For real-time autofocus of defocused images produced by Synthetic Aperture Radar (SAR), the twodimensional autofocus approach proposed in this study is used to correct the residual range cell migration and compensate for the phase error. Next, a block-wise Phase Gradient Autofocus (PGA) is used to correct the space-variant phase error. The Field-Programmable Gate Array (FPGA) design procedures, resource utilization, processing speed, accuracy, and autofocus are discussed in detail. The system is able to autofocus an 8K × 8K complex image with single precision within 5.7 s when the FPGA works at 200 MHz. The processing of the measured data verifies the effectiveness and real-time capability of the proposed method.